THE INFLUENCE OF SPIRITUAL LEADERSHIP ON LECTURER'S PERFORMANCE WITH THE MEDIATION OF ORGANIZATIONAL COMMITMENT AND WORK MOTIVATION - Al-Sakinah, Puteri Syarifah; Sudiro, Achmad; Djumahir, Djumahir (Jurnal Aplikasi Manajemen, 2020)
This study aimed to analyze the influence of the spiritual leadership of the performance of the lecturers, the influence of spiritual leadership on organizational commitment, influence organizational commitment to the performance of the lecturers, the influence of spiritual leadership to the work motivation, influence work motivation on the performance of the lecturers, the mediating role of organizational commitment in the spiritual leadership of the performance of lecturers, the mediating role of work motivation on the spiritual leadership of the performance of lecturers Universitas Pesantren Tinggi Darul Ulum Jombang. The population in this study is a lecturer in the. The sampling technique using proportional random sampling with a sample of 105 respondents. Data were analyzed using path analysis with SmartPLS 3.0.